PENENTUAN LOKASI SARANA PENGHUBUNG JAWA - BALI (SELAT BALI) SESUAI DENGAN KONDISI OPTIMAL GEOLOGI KELAUTAN - Usman, Ediar (Pusat Survei Geologi, 2007)
To decide the preferable location of a bridge or tunnel site connecting Jawa - Bali, marine geological survey on the sea floor of Bali Strait encompassing morphology and geology should be taken into consideration. Depression of 140 meters deep as a result of bathymetrical data recording can be observed. Besides this, the result of reflection seismic record gave a clear interpretation about materials constructing the sea floor, which consists of unconsolidated sediments of coral fragments and sands (such as mounded and slump type). The basement rocks were also found in a narrow basin with cliffs of about 100 to 140 metres deep going north - south direction. Keywords: marine geology, bathimetry, seismic interpretation, bridge location, Jawa – Bali